2016
DOI: 10.1080/10715762.2016.1234710
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities of ginsenoside Rg1 against cisplatin-induced hepatic injury through Nrf2 signaling pathway in mice

Abstract: Oxidative stress is mainly caused by reactive oxygen species (ROS). The damage causes a net stress on normal organs, leading to a gradual loss of vital physiological function. ROS, such as free radicals, represent a class of molecules which are derived from the metabolism of oxygen and exist inherently. However, excessive produced ROS can damage all aerobic organisms. Ginseng is one of the most commonly used alternative herbal medicines, also as a traditional Chinese medicine. The aim of this study is to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 40 publications
4
33
0
Order By: Relevance
“…It has been proven that Rg1 protects the brain against oxidative stress in many pathological conditions, such as Parkinson's disease [42,43], Alzheimer disease [44], D-galactose-induced brain aging [45], and others. Our previous study showed that Rg1's hepatic protection effect was mainly due to its antioxidant activity [35,46]. However, whether the efficacy of Rg1 against oxidative stress is involved in its antistroke capability has not been reported until now.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been proven that Rg1 protects the brain against oxidative stress in many pathological conditions, such as Parkinson's disease [42,43], Alzheimer disease [44], D-galactose-induced brain aging [45], and others. Our previous study showed that Rg1's hepatic protection effect was mainly due to its antioxidant activity [35,46]. However, whether the efficacy of Rg1 against oxidative stress is involved in its antistroke capability has not been reported until now.…”
Section: Discussionmentioning
confidence: 98%
“…The pellet and supernatant were treated separately. Brain samples were lysed by adding 10 times volume/quantity of cytosol extraction buffer A, and the subsequent protocol was the same as previously described [35].…”
Section: Ros Determinationmentioning
confidence: 99%
“…Liu L and et.al [88] had shown that Astragalus injection ameliorated the cisplatin-induced nephrotoxicity through regulating the Bax and Bcl-2 expression in mice. Other study [89] had shown that ginsenoside Rg1 also had antioxidant activities which ameliorated the cisplatin-induced hepatic injury through Nrf2 signaling pathway in mice. All these revealed that Astragalus and Ginseng could ameliorate chemotherapy related toxicity through enhancing the antimyelotoxicity activity, antiapoptotic, and antioxidant activities.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of detoxification and the metabolic pathways of the liver lead to liver injury and various liver diseases such as hepatitis, fatty liver disease, and fibrosis [2][3][4]. Currently, drugs used to treat liver injury are limited in efficacy or elicit many adverse reactions [5,6]. e drug pair Astragalus membranaceus (Huangqi)-Pueraria lobata (Gegen) was originally described in "Zhengzhihuibu," written during the Qing Dynasty of China.…”
Section: Introductionmentioning
confidence: 99%